Analisis Pelaksanaan Program Pengembangan SDM pada Departemen PT X - Muhammad Adriansyah; Nuzsep Almigo (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to assess the implementation of human resource development programs at the Human Resource Management and Development Department of Company X through technical assessments. The activity was carried out over three months from October to December 2025, involving participants from various fields such as utilities, maintenance engineering, and other fields. The methods used included participatory observation, informal interviews, and documentation. The results show that the program runs in a structured manner with the support of an HRIS system, coaching, and mentoring. Supporting factors include a clear organizational structure, defined role distribution, active involvement of MPSDM, and adequate facilities. The obstacles found include time constraints, variations in participant readiness, and technical system disruptions that cause implementation to not always go according to schedule. This activity provides an empirical overview for evaluating the effectiveness of the competency development program at Company X.